2016
DOI: 10.1103/physreve.93.063115
|View full text |Cite
|
Sign up to set email alerts
|

Binary-fluid turbulence: Signatures of multifractal droplet dynamics and dissipation reduction

Abstract: We study the challenging problem of the advection of an active, deformable, finite-size droplet by a turbulent flow via a simulation of the coupled Cahn-Hilliard-Navier-Stokes (CHNS) equations. In these equations, the droplet has a natural two-way coupling to the background fluid. We show that the probability distribution function of the droplet center of mass acceleration components exhibit wide, non-Gaussian tails, which are consistent with the predictions based on pressure spectra. We also show that the dro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 71 publications
0
15
0
Order By: Relevance
“…In addition, the external forcing properties f 0A,φ , and k f A,φ are also adjustable. Important dimensionless numbers here are as follows [25,31]: (4) Ch = ξ/L 0 , the Cahn number, which is the ratio of the interfacial thickness to the system size.…”
Section: A Basic Setupmentioning
confidence: 99%
“…In addition, the external forcing properties f 0A,φ , and k f A,φ are also adjustable. Important dimensionless numbers here are as follows [25,31]: (4) Ch = ξ/L 0 , the Cahn number, which is the ratio of the interfacial thickness to the system size.…”
Section: A Basic Setupmentioning
confidence: 99%
“…A recent study [44] has suggested that the SARS-CoV-2 virus remains viable in aerosols for nearly 3 h. Therefore, if the concentration of virus-laden aerosols is high in a poorly ventilated room, then we must employ more stringent socialdistancing norms than are in place now, even if people spend only tens of minutes together in such a room. The methods that we have developed can be applied, mutatis mutandis, (a) in sophisticated models for virus particles or droplets, e.g., those that use inertial particles [45,46] or multiphase flows [47,48], and (b) in turbulent flows that are not statistically homogeneous and isotropic. We will examine these in future work.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…An interplay between different phases is seen in many different terrestrial and astrophysical systems across a vast range of scales. This includes interactions between water vapour and air in the earth's atmosphere (Aronovitz & Nelson 1984;Pal et al 2016), the interface between hot and cold air in combustion (Bray & Cant 1991), solar corona mass ejections, loops, and coronal rain (Foullon et al 2011(Foullon et al , 2013Antolin 2020), warm and hot phases of the interstellar medium (ISM) (Begelman & Fabian 1990;Slavin et al 1993;Wolfire et al 1995a;Vázquez-Semadeni et al 2000;Audit & Hennebelle 2005;Hennebelle & Audit 2007;Glover et al 2010), neutral molecular/atomic, nebular and hot X-ray emitting regions in the Milky Way's wind (Fox et al 2015;Bordoloi et al 2017;Di Teodoro et al 2020), the circumgalactic medium (CGM) (Wolfire et al 1995b;Tumlinson et al 2011;Werk et al 2014;Tumlinson et al 2017;Marchal et al 2021) and the intracluster medium (ICM) (Tremblay et al ★ E-mail: rajsekhar.mohapatra@anu.edu.au (RM) † E-mail:mrinaljetti@gmail.com (MJ) ‡ E-mail: prateek@iisc.ac.in (PS) § E-mail: christoph.federrath@anu.edu.au (CF) 2018; Gendron-Marsolais et al 2018;Olivares et al 2019;Boselli et al 2019;Rose et al 2019;Vantyghem et al 2019Vantyghem et al , 2021. The mixing between these different phases is often governed by turbulent gas motions.…”
Section: Introductionmentioning
confidence: 99%